Authentication of vegetable oils. - Cunha, Sara C. (2014)
Authenticity of vegetable oils continues to be a challenge and the target of many studies. Consumers expectancy on healthier products that conform to the labelled information, and the vast amount of legislation a bout the correct characterisation and classification of vegetable oils have boosted a number of scientific works on this subject. Analytical t echniques to face this challenge are, at least, as manifold as ar e the ways of adulteration, ranging from classical determination of chemical parameters to highly sophisticated instrumental and molecular biology techniques. Rather than being an exhaustive revision of published works, the aim of the present chapter is to summarise: i) the analytical methods used in the determination of the main oil components such as fatty acids, triacylglycerols, phytosterols, tocopherols and tocotrienols, phenolic compounds, pigments and volatile compounds, emphasising their importance in authenticity evaluation; ii) the alternative tech niques based on spectroscopic.